Comparison of the Anterior Septal Line and Mitral Isthmus Line for Perimitral Atrial Flutter Ablation Using Robotic Magnetic Navigation. (1st February 2022) - Dang, Shipeng; Wang, Ru-Xing; Jons, Christian; Jacobsen, Peter Karl; Pehrson, Steen; Chen, Xu
Abstract : Background . Perimitral atrial flutter (PMAFL) is one of the most common macro-reentrant left atrial tachycardias. Mitral isthmus (MI) linear ablation is a common strategy for the treatment of PMAFLs, and anterior septum (AS) linear ablation has emerged as a novel ablation approach. We aimed at assessing the effectiveness of AS linear ablation using robotic magnetic navigation for PMAFL ablation. Methods . In this retrospective study, a total of 36 consecutive patients presented with AFL as the unique arrhythmia or accompanied with atrial fibrillation (AF) who underwent catheter ablation were enrolled. Patients were classified into two groups according to the different ablation strategies, the MI line group (10 patients) and the AS line group (26 patients). Results . The clinical baseline characteristics of patients in the two groups were nearly identical. There were no significant differences in procedure time (148.7 ± 46.1 vs. 123.2 ± 30.1 min, P = 0.058 ) or radiofrequency ablation time (25.9 ± 11.4 vs. 23.5 ± 12.6 min) between the two groups. Fluoroscopy time was longer in the MI line group (8.0 ± 4.4 vs. 5.1 ± 2.7 min, P = 0.024 ), and the acute success rate was higher in the AS line group versus the MI line group (96.2% vs. 70%, P = 0.025 ). The long-term freedom from arrhythmia survival rate was higher in the AS line group (73%) than in the MI line group (40%) after a mean follow-up time of 37.4 months with a 3-month blanking period (P = 0.049 ). Conclusions . AS linear ablation is an effective and safe strategy for PMAFL ablation using robotic magnetic navigation.